Safety, pharmacokinetics, and pharmacodynamics of RSLV-132, an RNase-Fc fusion protein in systemic lupus erythematosus: a randomized, double-blind, placebo-controlled study. (July 2017) - Burge, D J; Eisenman, J; Byrnes-Blake, K; Smolak, P; Lau, K; Cohen, S B; Kivitz, A J; Levin, R; Martin, R W; Sherrer, Y; Posada, J A
Blood-borne RNA circulating in association with autoantibodies is a potent stimulator of interferon production and immune system activation. RSLV-132 is a novel fully human biologic Fc fusion protein that is comprised of human RNase fused to the Fc domain of human IgG1. The drug is designed to remain in circulation and digest extracellular RNA with the aim of preventing activation of the immune system via Toll-like receptors and the interferon pathway. The present study describes the first clinical study of nuclease therapy in 32 subjects with systemic lupus erythematosus. The drug was well tolerated with a very favorable safety profile. The approximately 19-day serum half-life potentially supports once monthly dosing. There were no subjects in the study that developed anti-RSLV-132 antibodies. Decreases in B-cell activating factor correlated with decreases in disease activity in a subset of patients.